Strain Monitoring of Combustible Gas Implosion Test Based on Fiber Bragg Grating - Lei Gao; Qinghua Zhang; Erbing Li; Yangyang Sun; Zhenglin Zhang; Shikun Pu; Xiejun Cheng; Fengjuan Rong (Shock and Vibration)
Strain measurement is an important component in model tests of combustible internal explosions. Strain gauges are used to measure strain in traditional electrical measurement methods and have some limitations, such as susceptibility to electromagnetic interference, short life, and inability to distribute. Fiber Bragg gratings (FBGs) are developing into useful sensing tools that can respond to changes in stress, strain, and temperature by changing wavelengths. FBGs have excellent sensing performance, such as long life, antielectromagnetic interference, easy networking, and good reusability. In this paper, FBG sensors are applied to strain monitoring in ethylene flammable implosion experiments. In the ethylene flammable implosion tests, an FBG was placed on the inner surface of the bottom plate of the rectangular steel test device near the detonation vent by the sticking method. The reliability and repeatability of the strain change of the FBG affected by detonation overpressure and combustion were tested at this point. Four explosion tests were carried out. The test results showed that FBG sensors could obtain stable and reliable strain data in all four tests. The strain variation reflects the development of overpressure and combustion in the whole process from ignition. For the strain amplitude formed by overpressure, the minimum was 1.449 με (the third test), and the maximum was 48.181 με (the fourth test).For the strain amplitude step change formed by the deflagration flame front passing the measurement points, the minimum was 1.673 με (the second test), and the maximum was 19.724 με (the fourth test).The strain amplitude produced by the deflagration temperature effect in the four tests ranged from 72.803 με (the first test) to 143.381 με (the fourth test).The results show that FBG sensors can provide reliable and effective strain monitoring data for the experimental study of flammable implosions.